Assessment of Bone Mineral Density (BMD) among general population of District Khuzdar, Baluchistan Pakistan (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the frequency of osteoporosis and osteopenia among the general population of District Khuzdar, Baluchistan Pakistan.Methods: This was a cross-sectional study and the data was collected on “World Osteoporosis Day” 20th October 2019 during an awareness session arranged by Shaheed Baz Muhammad Kakar Foundation at Baluchistan University of Information Technology, Engineering and Management Sciences Khuzdar Campus. The bone mineral density of all participants fulfilling the inclusion criteria was determined with DMS PEGASUS SMART Bone Densitometer. The T-scores were measured based on the readings of each individual and further characterized as Normal (+1 to -1 Standard Deviations), Osteopenia (-1 to -2.5 Standard Deviations), and Osteoporosis (